Feeding transgenic plants that express a tolerogenic fusion protein effectively protects against arthritis. Issue 4 (25th September 2015) - Hansson, Charlotta; Schön, Karin; Kalbina, Irina; Strid, Åke; Andersson, Sören; Bokarewa, Maria I.; Lycke, Nils Y.
Summary: Although much explored, oral tolerance for treatment of autoimmune diseases still awaits the establishment of novel and effective vectors. We investigated whether the tolerogenic CTA1(R7K)‐COL‐DD fusion protein can be expressed in edible plants, to induce oral tolerance and protect against arthritis. The fusion protein was recombinantly expressed in Arabidopsis thaliana plants, which were fed to H‐2 q ‐restricted DBA/1 mice to assess the preventive effect on collagen‐induced arthritis (CIA). The treatment resulted in fewer mice exhibiting disease and arthritis scores were significantly reduced. Immune suppression was evident in treated mice, and serum biomarkers for inflammation as well as anticollagen IgG responses were reduced. In spleen and draining lymph nodes, CD4 + T‐cell responses were reduced. Concomitant with a reduced effector T‐cell activity with lower IFNγ, IL‐13 and IL‐17A production, we observed an increase in IL‐10 production to recall antigen stimulation in vitro, suggesting reduced Th1, Th2 and Th17 activity subsequent to up‐regulated IL‐10 and regulatory T‐cell (Treg) functions. This study shows that edible plants expressing a tolerogen were effective at stimulating CD4 T‐cell tolerance and in protecting against CIA disease. Our study conveys optimism as to the potential of using edible plants for oral treatment of rheumatoid arthritis.